eQTL mapping identify insertion and deletion specific eQTLs in multiple tissues - Huang, Jinyan (Nat Commun, 2015)
GenomeC wide gene expression quantitative trait loci (eQTL) mapping have been focused on single nucleotide polymorphisms and have helped interpret findings from diseases mapping studies. The functional effect of structure variants, especially short insertions and deletions (indel) has not been well investigated. Here we imputed 1,380,133 indels based on the latest 1000 Genomes Project panel into 3 eQTL datasets from multiple tissues. Imputation of indels increased 9.9% power and identified indel specific eQTLs for 325 genes. We found introns and vicinities of UTRs were more enriched of indel eQTLs and 3.6 (singleC tissue)C 9.2%(multiC tissue) of previous identified eSNPs were taggers of eindels. Functional analyses identified epigenetics marks, gene ontology categories and disease GWAS loci affected by SNPs and indels eQTLs showing tissueC consistent or tissueC specific effects. This study provides new insights into the underlying genetic architecture of gene expression across tissues and new resource to interpret function of diseases and traits associated structure variants.